La justicia indígena en la Legislación Ecuatoriana y su contraposición con la justicia ordinaria y la Constitución, instaurando la “vindicta pública” y la impunidad - Arguello Dávila, Diego Oswaldo (2016)
As was previously noted in the problem statement, the interpretation and application of embedded "Indigenous Justice" in ART.171 of the Constitution of Ecuador and its apparent force opposed to the regular courts and Constitutional precepts controversy necessarily requires us to be attentive to different changes in the legal and social actions may arise in the daily development of the country. As active participants of these changes and even more as a future attorney of the Republic of Ecuador, it is necessary and important for a whole carefully analyze these rules in handling the administration of justice is fair and necessary to discuss and socialize benefit the community. Poor interpretation and application of these rules in the background might have other intentions beyond the collective interest, requires a thorough review of the same, as they directly affect the environment and context of today's society, to the extent that such laws ( as I said above ) could be routed to other interests of ideological character and why not tell politicians, strictly impairment of the sublime interests of society and the individual rights of the people, putting at serious risk the legal certainty and therefore, State institutions as such. Unfortunately, little attention has been paid to the legislature against this problem, perhaps responding to immediate interests of power, has caused a growing distrust by those of a rapt and worryingly, are threatened every day, one way or another of our rights referred in the Constitution, International Human Rights Organizations and the Law in general. " There is no doubt that equality before the law must be understood in terms of the essential characteristics of Ecuadorians , for which reason there is no legal justification for discrimination or privileges or whose foundation is factors related to characteristics of birth, age, sex, ethnicity , color, social origin, language , religion , political affiliation , economic status, or other . For this and many other reasons, and; as a result of this dichotomy established in the management of the administration of justice in our country, I can see that it is right and necessary to form an active part of the respective changes that may occur. For legal certainty requires the provision of a response in accordance with law for the different conflicts that arise in human society ; because only in this way stability occurs , which leads to getting the final fidelity to the principle of legality. The purpose of this research study of this thesis, it appears substantially in fact analyzed from the point of view of legal-regulatory effectiveness of the implementation of the " Indian Justice " (if you can call it justice ) and their correct interpretation and application. For this; ( repeat ) aware of the conflict that involves proper and effective implementation of the rules , and always strictly attached to the constitutional provision and their respective regulations but primarily in the legal field , I would analyze and deepen the aforementioned issue , hoping to contribute to this study, the formation of a system or model management more fair and appropriate , consistent as well with the historical reality of the country and especially in accordance with the guiding principles emanating from the Constitution , International Human Rights Organizations Justice, and Law in general